Karakteristik Analisis Wacana Kritis Tindakan Dalam Cerpen Dolop Karya Akhmad Sekhu - Kresna Tribuana Putri Phroshak; Nurul Kurniawati; Mifta Nur Aini (Center of Language and Cultural Studies, 2021)
Critical discourse analysis (CDA) in the perspective of Teun A. Van Dijk, Fairclough, and Wodak is divided into five characteristics, namely action, context, history, power, and ideology. The study object of CDA can be varied, one of which is literature. This research will examine the characteristics of CDA, namely action inside Dolop short story by Akhmad Sekhu. In this case, the form of action will be classified into a form of nonverbal action and verbal action, then it will be classified again into a form of action that reflects life as a dolop, an impostor who disguised as an ordinary citizen. Dolop short story is written by Akhmad Sekhu, this short story is published at Laman Cerpen Digital Kompas on 22nd of October 2020. This study used a qualitative research design with descriptive methods for analyzing the data until then it was found the results that in Dolop short story contains sixteen forms of nonverbal action and nineteen forms of verbal action that reflect life as a dolop. The gaps of this research are focusing on one of the characteristics of CDA which is action, meanwhile in contrast to other studies usually focusing on all the characteristics of CDA.